Do the dimensions of the hard palate have a relationship with the volumes of the upper airways and maxillary sinuses? A CBCT study - Murilo Miranda-Viana; Deborah Queiroz Freitas; Alessiana Helena Machado; Amanda Farias Gomes; Yuri Nejaim (BMC, 2021)
Abstract Background As the hard palate is a central structure of the skull, and its close relationship with the nasal cavity, oral cavity, and maxillary sinuses, it would be of interest to study if there is a relationship between this bone and other structures of the stomatognathic system. Thus, this study aimed to assess the dimensions of the hard palate and associate them with sex, and skeletal and breathing patterns. Also, to investigate if there is a relationship between these dimensions and the volumes of the upper airways and maxillary sinuses. Methods Two hundred and ninety-eight CBCT scans of patients were classified according to sex, and skeletal and breathing patterns. Then, the linear dimensions of width and height of the hard palate at the regions of the first premolars and first molars, and the volumes of the upper airways and maxillary sinuses were measured using the CS 3D Imaging and ITK-SNAP software, respectively. Data were submitted to multi-way analysis of variance and linear regression, with a significance level of 5% (α = 0.05). Results Sex and facial type influenced the hard palate dimensions (p < 0.05). Males had greater width and height of the hard palate than females (p < 0.0001). It was observed greater width for brachycephalics at the first premolars region (p = 0.0032), and greater height for dolichocephalics at the first premolars (p = 0.0154) and first molars (p = 0.0038) regions. Skeletal malocclusion and breathing pattern did not influence the measurements of the hard palate (p > 0.05). There was a significant relationship between the width and height of the hard palate at the premolar's region and the total volume of the upper airways (p = 0.018, and p = 0.038), and between both dimensions of the hard palate at the molar's region and the total volume of the maxillary sinuses (p < 0.0001). Conclusions The hard palate dimensions are influenced by sex and facial type, but not by skeletal malocclusion or breathing pattern. Also, there is an association between these dimensions and the volumes of the upper airways and maxillary sinuses.